2017
DOI: 10.1111/sltb.12336
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Suicide and Suicidal Behavior Relevant to Emergency Health Care Settings: A Systematic Review of Post‐2007 Reviews

Abstract: Suicide is a global public health problem, and with recent economic and societal changes, there may be emerging risk factors unrecognized by health care professionals. The aim of this systematic review was to update existing suicide risk factor literature applicable to emergency health care settings. A total of 35 articles identified from PsycINFO, CINAHL, and Medline met the inclusion criteria. Results supported the significance of existing suicide risk factors and identified emerging risk factors. The review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 44 publications
0
22
0
3
Order By: Relevance
“…Furthermore, the review did not investigate protective factors of suicide with transgender individuals indicating a literature gap, which has also been identified in the risk factor literature (McClatchey, Murray, Rowat & Chouliara, 2017), and as nearly half of trans people under 26 have attempted suicide (Stonewall, 2017), this is an area of research with a high need of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the review did not investigate protective factors of suicide with transgender individuals indicating a literature gap, which has also been identified in the risk factor literature (McClatchey, Murray, Rowat & Chouliara, 2017), and as nearly half of trans people under 26 have attempted suicide (Stonewall, 2017), this is an area of research with a high need of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A recently conducted, large meta‐analysis also demonstrated that prediction of suicide based on historically established risk factors, over an average of 10 years, was only slightly better than chance at predicting suicidal outcomes (Franklin et al., ), thereby putting the risk factors we use as part of our suicide risk assessment into question. There is also evidence to suggest newer risk factors that are still emerging (McClatchey, Murray, Rowat, & Chouliara, ). As such, these risk factors are not accounted for in conventional risk scales.…”
Section: Discussionmentioning
confidence: 99%
“…Associados ao problema estão fatores gerais como a desigualdade de renda, o baixo nível de escolaridade, o desemprego e a presença de transtornos mentais como, por exemplo, a ansiedade e a depressão (4)(5) . No entanto, existem fatores condicionantes que são mais comuns entre indivíduos de determinado gênero.…”
Section: Introductionunclassified
“…Dentre eles, podem-se citar o elevado consumo de álcool e outras substâncias, a presença de problemas financeiros, criminais e àqueles relacionados com o trabalho entre os homens, ao passo que, entre as mulheres o suicídio se dá mais devido aos problemas de saúde física, questões familiares, conflitos conjugais e relacionamentos abusivos. Ademais, a literatura reporta amplamente que as mulheres estão mais expostas a maus-tratos e violências, especialmente a sexual, os quais contribuem para os maiores índices de tentativas de suicídio nesta população (5)(6)(7) .…”
Section: Introductionunclassified